Where Is "the South"? Assessing the Meaning of Geography in Politics. Issue 5 (September 2019) - Springer, Melanie J.
The use of geographic classifications to make empirical or theoretical generalizations is common in political science research. Yet, in most cases, these groupings, in and of themselves, lack broader meaning. Offering an in-depth example of the American South, this study demonstrates the need to scrutinize the qualities we are actually interested in when using geographic classifications to explore political trends. The article begins by discussing the many ways that "the South" has been defined in the existing literature. Then, it evaluates the theoretical and empirical consequences of these various definitions using examples focused on discriminatory practices, voter turnout, and civil rights roll call votes. This evidence demonstrates the importance of grounding one's definition in substantive metrics and historical context over and beyond basic geography. The study concludes with a discussion of its broader implications that apply to several topics of interest and research strategies.